Kejahatan Lingkungan Oleh Korporasi: Mencari Bentuk Pertanggungjawaban Korporasi Dan Pemimpin/Pengurus Korporasi Untuk Kejahatan Lingkungan Di Indonesia? - Wibisana, Muhammad Andri Gunawan (UI Scholars Hub, 2016)
It is very likely that most environmental crimes involve corporation, in the sense that the crimes were conducted within the scope of corporation and on behalf of the corporation. This contribution attempts to answer the questions of how corporate criminal liability has evolved in several jurisdictions, and how this concept has been interpreted and implemented in Indonesia. The contribution explains the development of corporate criminal liability, and classifies it into liability for corporation and liability for corporate officers. Based on such theoretical foundations, the contribution critically analyses the formulation of corporate criminal liability and officers' liability in various legislations related to environmental protection and in various court decisions in Indonesia. It is observed that some laws and rulings failed to make a clear distinction between criminal liability for corporation and that for its high ranking officers. The failure result in some rulings where a corporation being held liable although it was not a defendant, or a director was likely to be put in jail although he was not a defendant. The contribution recommends some changes in corporate and officers' criminal liability in Indonesia. In particular, this contribution criticizies the use of individual criminal liability, and argues that to hold an officer liable the government needs to prove the contribution of the officer in the criminal conduct.